Numerical analysis of the possibility of co-firing ammonia in a coal-fired power boiler - Kiedrzyńska, Aleksandra; Glot, Beata; Jóźwiak, Piotr (Instal, 2025)
The paper presents the results of numerical simulations of the ammonia co-combustion process using the OP-650 power boiler as an example. Using simulation methods, the place of NH3 introduction to the boiler was optimized and the maximum acceptable share of ammonia in the total heat share of the fuel to the boiler was determined. The aim was to find a compromise between maximizing the amount of ammonia introduced and maintaining stable combustion in the combustion chamber and an acceptable level of pollutant emissions. The calculations showed a positive effect of ammonia co-combustion on carbon dioxide emissions from the power boiler. Co-combustion of 40% (of the boiler thermal power) of ammonia resulted in a reduction of CO2 emission factor below 550 kg/MWh. The calculations also revealed a significant relationship between the location of ammonia injection and nitrogen oxides emissions, indicating the most advantageous position for introducing the new fuel is at lower row burners of the analyzed boiler.
Keywords: ammonia co-firing; pulverized coal boiler; NOx emissions; CO2 emissions; CFD simulations; decarbonisation